Exploring gut microbiota and spinal cord injury: pathogenesis, treatment strategies and prospects - Chen, Qin; Zhong, Mingliang; Lin, Ye (Frontiers in Immunology, 2025)
Spinal cord injury (SCI) is a disabling central nerve system (CNS) injury, often caused by factors such as traffic accidents, falls from heights, violent trauma, and sports injuries, commonly resulting in permanent loss of motor and sensory function below the level of injury. Increasing evidence suggests that gut microbiota influences the occurrence and development of CNS diseases through the brain-gut axis. Recent studies indicate that patients with SCI frequently exhibit gut microbiota dysbiosis. Changes in gut microbiota can lead to gut barrier disruption, triggering neurogenic inflammatory responses, thereby hindering recovery after SCI, while reshaping gut microbiota may benefit the recovery of intestinal function and neurofunction after SCI. In this review, we summarize emerging literature on the role of microbiota after SCI. We elucidate the intrinsic connection between gut microbiota and SCI, explore the role of gut microbiota in the pathogenesis of SCI, and investigate potential intervention strategies targeting gut microbiota, including probiotic therapy, fecal microbiota transplantation (FMT), and regulation of metabolites, aiming to provide theoretical basis and translational prospects for developing innovative microecological targeted therapeutic approaches.